Nafkah Anak dalam Perkara Cerai Pasca Sema No. 4 Tahun 2016 Pada Pengadilan Agama Bangkinang - Mardhotillah, Dayu Annisa; Johari, Johari; Wahidin, Wahidin (USRATY : Journal of Islamic Family Law, 2024)
The determination of child support rights in the Bangkinang Religious Court following the issuance of SEMA Number 4 of 2016, as well as to evaluate the implementation of child support determinations according to the theory of legal certainty. This study is a field research conducted at the Bangkinang Religious Court, where the author gathers concrete data and information through observations and interviews. The focus of this research is on the implementation of SEMA Number 4 of 2016, particularly regarding the authority of judges in determining child support post-divorce in the divorce lawsuit cases of 2023 at the Bangkinang Religious Court. This is crucial because there are several rulings that do not specifically stipulate the father's obligation to provide for his child. Judges should have the ex officio right to determine the nominal amount of child maintenance that must be borne by the father, in accordance with the provisions outlined in SEMA No. 4 of 2016. The lack of clarity regarding the father's obligation towards children after divorce has the potential to cause legal uncertainty in the fulfilment of child maintenance, which in turn can interfere with the welfare of children after divorce. Therefore, this study recommends that judges provide clearer decisions regarding the amount of child maintenance, while still considering the father's financial capacity. In addition, any regulations or procedures relating to the implementation of court administration need to be carefully considered, given their impact on the welfare of children after the decision.